1991
DOI: 10.1093/nar/19.18.4857
|View full text |Cite
|
Sign up to set email alerts
|

Physical map of chromosomal and plasmid DNA comprising the genome ofLeptospira interrogans

Abstract: The size and physical structure of the Leptospira interrogans genome was characterized using contour-clamped homogenous electric field (CHEF) gel electrophoresis. The L. interrogans genome is approximately 4750 kb in size and is composed of two molecular species of DNA: a 4400 kb chromosome; and a 350 kb plasmid, pLIN1. A physical map of the chromosome was constructed with the restriction enzymes NotI and SfiI. A physical map of pLIN1 was constructed with ApaI, NotI, Sse83871, SgrAI, and SmaI. Both the L. inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 18 publications
3
56
0
Order By: Relevance
“…However, the physical map constructed in this study demonstrates the circular nature of the L. interrogans chromosome. In addition, during the course of these studies, the physical map of the chromosome of L. interrogans serovar pomona strain Kennewicki was reported and shown to be circular (41 In agreement with the results of others (36,41), our analysis of the whole genome of L. interrogans showed the presence of an extrachromosomal element. A 350-kb band is seen in undigested preparations and in AscI digests of L.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, the physical map constructed in this study demonstrates the circular nature of the L. interrogans chromosome. In addition, during the course of these studies, the physical map of the chromosome of L. interrogans serovar pomona strain Kennewicki was reported and shown to be circular (41 In agreement with the results of others (36,41), our analysis of the whole genome of L. interrogans showed the presence of an extrachromosomal element. A 350-kb band is seen in undigested preparations and in AscI digests of L.…”
Section: Discussionsupporting
confidence: 90%
“…Taylor et al suggested that the L. interrogans chromosome is linear, fragmented, and approximately 3.1 Mbp (36). However, we found it to be circular and 4.6 Mbp, in agreement with our earlier results (2) and the report of Zuerner (41). Such a map will provide a point of reference from which the linkage of specific genes can be established.…”
supporting
confidence: 93%
See 3 more Smart Citations